Generality (‘Āmm) in the Legal Spectrum of Conventional Law and Sharī’ah versus Common Noun in English Grammar (A Comparative Jurisprudential and Linguistic Approach) (Al Basirah, 2020)
Generality, indeed, is an essential character of every legal system;otherwise, they begin to lose, at ground level, their practicality andefficiency. Both Sharī‟ah and the conventional legal system, therefore,employ generality as a matter of jurisprudential principle, as it ensures„equality before law‟ and „justice for all‟ without any discrimination.Putting great belief in generality, legal experts, predominantly, thoseexercising authority in their corresponding jurisprudence, proposegenerality in the legal texts – leaving no space for any compromise underthe umbrella of legal interpretation, both at textual and contextual levels.On the other hand, the Common Noun of English grammar, showinggenerality of meaning, corresponds with generality in English law and„āmm (general terms) in Sharī‟ah. Though, the two legal systems haveincluded the general rules, nevertheless, the Islamic legal system uses thegeneric nature of words in a better way under a fine structure andmechanism. Apart from generality, both the systems identify certainrestrictions (khāss) under specific conditions in order to deal a myriad ofsituations. The present work, primarily, aims at comparing the generalrules, adopted by both the systems and, thus, at highlighting commonalitiesamong them. It also intends to pinpoint the differences of their adaptationand application of the same rule. The findings, reached herein, show thatboth present similarities/commonalities and, of course, differences, albeitinsignificant and unnoticeable. Sharī‟ah (Islamic law), however, is moresuperior in its approach and application of general words in its legal textsand contexts. Moreover, this work suggests new dimensions, as guidelines,for experts in the interpretations of their laws concerned. As the study isqualitative in nature, therefore, discourse analysis technique (narrowly canbe called descriptive methodology), an appropriate method, herein, hasbeen used for the investigation of the issue under probe.
Keywords: āmm, khāss, law, Sharī‘ah, common noun, jurists, jurisprudence, Usūl-al-Fiqh.